The Campus Canopy, 1940-03-08 - The Campus Canopy, The Georgia State Woman's College (The Georgia State Woman's College, 1940)
The Campus Canopy, March 8, 1940. Vol. 6, No. 16. Sara Grabutt Elected May Queen -- Burns -- Williams, Martin Win Class Offices -- Sara Garbutt And Louise Bell To Reign At May Day, Play Day Festivities May 4 -- "Little Willie" Will Become A Medium Of Luck -- Margaret Burns, Grace Williams And Sara Martin Will Be Class Presidents -- Philharmonic Hears Cincinnati Symphony Group -- N. Y. A. Students Strike High Point A s Scholars -- Punke Attends N E A Convention -- Do You Hunt Short Cuts In Making “A ” Average?
Digitized from original print, Valdosta State University Archives and Special Collections, January 9, 2017.
Keywords: The Georgia State Woman's College; GSWC; Valdosta State College; VSC; Valdosta State University; VSU; 1940s; 1940; The Campus Canopy